1985
DOI: 10.1073/pnas.82.4.1050
|View full text |Cite
|
Sign up to set email alerts
|

Parathymosin alpha: a peptide from rat tissues with structural homology to prothymosin alpha.

Abstract: A peptide, parathymosin a, containing %105 amino acid residues, has been isolated from rat thymus, and the sequence of the first 30 residues at the NH2 terminus has been determined. In this region, it shows 43% structural identity with thymosin a, and prothymosin a. The common sequences do not include residues 2-9, which accounts for the poor reactivity of parathymosin a with an antibody directed against this epitope in thymosin a1. Parathymosin a appears to modulate the action of prothymosin a in protecting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
26

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 11 publications
2
36
0
26
Order By: Relevance
“…It was reported that the expression of ProTα was higher in proliferative cells than that in quiescent cells. And in adults, the more proliferative tissues exhibited higher levels of ProTα (Haritos et al, 1985). All these studies suggest that carp ProTα may exhibit similar function in carp liver as that in mammals, which needs to be further studied.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…It was reported that the expression of ProTα was higher in proliferative cells than that in quiescent cells. And in adults, the more proliferative tissues exhibited higher levels of ProTα (Haritos et al, 1985). All these studies suggest that carp ProTα may exhibit similar function in carp liver as that in mammals, which needs to be further studied.…”
Section: Discussionmentioning
confidence: 81%
“…The expression of ProTα b during infection was significantly up-regulated in spleen which was the main peripheral immune organ in carp, followed in kidney, intestine and peripheral blood which were all immune-related organs. Since 1994, ProTα has been reported to inhibit the replication of virus and the reproduction of cancer cells by inducing immune cells (Baxevanis et al, 1994(Baxevanis et al, , 1995Haritos et al, 1985;Romani et al, 2004). Thymosin α1, corresponding to the first 28 amino acid residues of ProTα, was reported to increase the expression of MHC I which presented endogenous peptides to cytotoxic T cells to kill the virally infected cells as well as some cancer cells (Giuliani et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ProT has been reported to be more effective than thymosin α1 in the protection of mice infected with Candida albicans, suggesting that the biological activity of ProT is not solely determined by its N-terminal region that includes the thymosin α1 fragment. 3 Bladder cancer, especially presenting as superficial disease, is responsive to immunotherapeutic agents, such as BCG, and may represent a good candidate for immunological intervention. Indeed, in the murine MBT-2 bladder tumor model, irradiated, interleukin-2 or granulocyte-macrophage colony-stimulating factor genemodified MBT-2 cells were capable of curing about half of the mice bearing wild-type MBT-2 tumors and engendered protective immunological memory in the cured mice.…”
Section: Introductionmentioning
confidence: 99%
“…Haritos et al (10,14) initially isolated MTI-II from rat thymus as parathymosin, a homolog of the protein prothymosin ␣ (PT␣). MTI-II/ parathymosin shares 46% identity with PT␣ (14), but the two proteins show a reciprocal tissue distribution in rats (10,12).…”
mentioning
confidence: 99%